2016
DOI: 10.1002/lt.24399
|View full text |Cite
|
Sign up to set email alerts
|

Left lobe graft poses a potential risk of hepatic venous outflow obstruction in adult living donor liver transplantation

Abstract: Hepatic venous outflow obstruction (HVOO) is a critical complication after living donor liver transplantation (LDLT).This study aimed to evaluate the incidence of HVOO and the risk factors for HVOO in adults. From 2005 to 2015, 430 adult LDLT patients (right lobe [RL] graft, 270 patients; left lobe [LL] graft, 160 patients) were enrolled and divided into no HVOO (n 5 413) and HVOO (n 5 17) groups. Patient demographics and surgical data were compared, and risk factors for HVOO were analyzed. Furthermore, the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 34 publications
(92 reference statements)
2
34
0
Order By: Relevance
“…Moreover, these reasons may explain why the incidence of HVOO was relatively higher in our hospital for the pediatric cases, in which left lobe/left lateral segment grafts were used, as well as for adult cases undergoing left lobe implantation. In agreement with this idea, Kitajima and associates 7 recently reported that left lobe implantation was an independent risk factor for post-LDLT HVOO.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Moreover, these reasons may explain why the incidence of HVOO was relatively higher in our hospital for the pediatric cases, in which left lobe/left lateral segment grafts were used, as well as for adult cases undergoing left lobe implantation. In agreement with this idea, Kitajima and associates 7 recently reported that left lobe implantation was an independent risk factor for post-LDLT HVOO.…”
Section: Discussionsupporting
confidence: 52%
“…3 Early-onset HVOO can result from a number of factors, such as a tense suture line, bending of a redundant hepatic vein, mismatch between the size of recipient and graft, low recipientto-donor body mass index ratio, compression of the IVC by a large graft, and thrombosis. 2,4,7 In contrast, the cause of late-onset HVOO includes intimal hyperplasia, fibrosis development secondary to inflammation (ie, abscesses or bile leaks), twisting of an anastomosis, external compression due to graft growth, and anastomosis strictures secondary to fibrotic changes in the dissection field. 2,4 After a first description of the standard end-toend cavocaval anastomosis technique for DDLT, researchers were stimulated to develop improved anastomosis techniques, such as the piggyback and the modified piggyback to minimize the rate of HVOO.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively lower rate of complications after LT in our institution may be contributed to a few factors 8 . LTs using the left liver lobe and pre-existing hepatitis C are known as risk factors for long-term graft failure 9 , 10 . The most common indication for living donor LT in our institution was hepatitis B with most of these patients receiving LTs using the right liver lobe.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports suggested that stent placement should be considered after two or three failed balloon venoplasties for HVOO after pediatric LDLT . Sakamoto et al reported a pediatric case with HVOO recurrence requiring stent placement, whose liver biopsy revealed severe fibrosis in zone 3 at 1 year after the last stent placement procedure.…”
Section: Discussionmentioning
confidence: 99%